Green solvent system for isolation of biopolymers from Mentha arvensis distilled biomass and saccharification to glucose for the production of methyl levulinate. (July 2022) - Kumar, Deepak; Sharma, Praveen Kumar; Prakash, Om; Chaturvedi, Shivani; Singh, Suman; Sai Kumar, Ch Mohan; Nannaware, Ashween Deepak; Kalra, Alok; Rout, Prasant Kumar
Abstract: Cornmint ( Mentha arvensis ) is cultivated to produce essential oil, which consists of about 75% of menthol. Fresh biomass is hydrodistilled for ∼5 h to obtain essential oil (1%), and the rest of the pre-treated biomass (99%) is generated as waste. A novel, green and economical two-step process has been developed using a mixture of imidazole (IM:1 M)-p-toluene sulfonic acid (pTSA:1.2 M), and IM (0.2 M)-20%NH3 for the separation of lignin and hemicellulose, respectively. The lignin and hemicellulose were isolated from the respective solution by precipitation, and final undissolved solid residue was obtained as cellulose. This process was scaled-up, recovering cellulose (38%), hemicellulose (27%), and lignin (14%) using 7 L double jacketed reactor. The processing parameters such as temperature, solvent ratio, and time were optimized using single factorial design mathematical model for the isolation of biopolymers. Further, cellulose was enzymatically biotransformed to glucose through submerged and solid-state fermentation (SSF) using Trichoderma reesei, T. harzianum (TH, TH10), and T. atroviride . Isolated cellulose was produced 61.5% of glucose at 30 °C, pH 5 in 72 h through SSF process using TH10 strain. This glucose solution was transformed to methyl levulinate (74%) under aqueous-methanol (5:1) solvent system for 2 h at 160 °C using La(OTf)3 .H2 O catalyst. Graphical abstract: Image 1